Government Roadmap for IPv4 to IPv6 Network Migration: A Case of Nepal - Dawadi, Babu Ram; Shakya, Subarna; Khanal, Ananda Raj (Journal of the Institute of Engineering, 2016)
The recent breakthrough in Information and Communication Technologies(ICT) make the internet and e-mail as a basic service for the people of every country. The rapid growth in internet users and ICT market by the development of smart devices increase the challenges in hardware and networking management as well as effciency on software and services. Hence migration to new and latest technologies like software defned networking, cloud computing and IPv6 addressing become inevitable for the service providers throughout the world. Asia is the frst continent where shortage of IPv4 was faced. APNIC announced the depletion of IPv4 address on April 2011 [1]. Similarly the IPv4 pool on other Regional Internet Registries have already fnished except AFRINIC. With the shortage of address, Asian countries like Japan, China, India, Malaysia etc... have developed the government policies and national roadmap. They are under monitoring and evaluation of the private and public networks. European union and the American government put forward the priority on IPv6 network migration. In this paper a migration roadmap for Nepal is being proposed after reviewing the world’s IPv6 migration status, other countries policy and roadmap for migration planning as well as survey carried out with Nepalese telecom, internet market and government agencies . Journal of the Institute of Engineering, 2015, 11(1): 67-78